IOT-BASED SOLAR POWER GENERATION SYSTEM DESIGN FOR REAL-TIME MONITORING - Farida Arinie; Sulaiman Sulaiman; Usman Tahir; Nurjannah Nurjannah; Ardi Azhar Nampira (Journal of Moeslim Research Technik, 2025)
The increasing demand for renewable energy sources has led to the growing adoption of solar power systems. However, efficient monitoring of these systems is essential for optimizing performance and maintenance. Integrating Internet of Things (IoT) technology offers potential solutions for real-time monitoring and management of solar power generation. This research aims to design an IoT-based solar power generation system that enables real-time monitoring of energy production, system performance, and environmental conditions. The goal is to enhance the efficiency and reliability of solar energy systems through advanced data analytics. A prototype system was developed using IoT sensors to collect data on solar panel output, temperature, and weather conditions. The system utilized a microcontroller for data processing and transmission to a cloud platform for real-time visualization and analysis. User-friendly dashboards were created to facilitate monitoring and alert users to potential issues. The findings demonstrated that the IoT-based system effectively monitored solar power generation, providing real-time data on energy output and environmental factors. The system achieved an accuracy of 95% in data reporting, allowing for timely interventions to optimize performance. Users reported improved decision-making capabilities based on the insights gained from the monitoring system.